Observasi Peran Bahasa Indonesia dalam Edukasi Kesehatan Lingkungan untuk Wisatawan dan Masyarakat Lokal Dipantai Oluhuta Kec. Kabila Bone, Kab. Bone Bolango, Gorontalo - Dali, Meilina Widya; Monorfa, Fidyawati; Huruji, Haikal; Tuna, Hasriyanti; Isyandy, Rindi; Koniyo, Siti Khumairoh N.; Razak, Aida Salsabila; Manangin, Jangnara; Nupu, Dilfadila W.; Hasim, Fidyawati S.; Djumura, Fadilah; Djafri, Salsabila; Ibrahim, Muthmainnah Putri H.; Rares, Athalia Eliseba; Pobela, Anatasya (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Indonesian is the official language of the country and plays a crucial role in conveying environmental health information and education in public spaces, particularly at tourist destinations. This study aims to identify the role of Indonesian in facilitating environmental health education for tourists and the community at Olohuta Beach Tourism, Kabila Bone District, Bone Bolango Regency. The research method used was descriptive with a qualitative approach. Data collection techniques included observation, interviews, and documentation. The results showed that Indonesian was used on health warning boards and in direct communication between managers, vendors, and visitors. The use of clear, polite, and easy-to-understand Indonesian language increased visitors' understanding and awareness of the importance of maintaining environmental cleanliness and health. Thus, Indonesian plays a strategic role as a medium for environmental health education in supporting public health efforts at the Olohuta Beach tourist destination.